Bilberry anthocyanin extracts enhance anti-PD-L1 efficiency by modulating gut microbiota. Issue 4 (25th March 2020) - Wang, Luoyang; Jiang, Guoqiang; Jing, Nan; Liu, Xuerun; Li, Qicheng; Liang, Wei; Liu, Zheng
Abstract : Bilberry anthocyanin extracts change the gut microbiota and enhance the anti-tumor efficiency of the PD-L1 antibody. Abstract : The undesirable low response rate is a major hurdle to garnering the maximum potential of immune checkpoint inhibitors in cancer treatments. Recent advances in exploring the effects of intestinal flora on the medical efficacy of immune checkpoint blockade have shed new light on the application of immune checkpoint inhibitors. Inspired by the prebiotic role of anthocyanin-rich extracts, we propose using bilberry anthocyanin extracts to modulate the composition of gut microbiota and eventually, promote the efficiency of immune checkpoint inhibitors. This study demonstrates the effectiveness of orally administered bilberry anthocyanin extracts in enhancing the anti-tumor efficiency of the PD-L1 antibody in the experimental mouse MC38 tumor model. We observed an increase in the fecal abundance of Clostridia and Lactobacillus johnsonii and improved effective community diversity. These findings reinforce the importance of intestinal flora composition and open up unprecedented opportunities in using natural compounds to enhance the efficacy of immune checkpoint inhibitors.